Proenkefalin A and protachykinin in ischemic neurological complications after cardiac surgery - Milan Skitek; Aleš Jerin (Medicinski glasnik, 2016)
Aim: The evaluation of biomarkers of acute ischemic brain injury following surgical revascularization of the heart with the use of the heart-lung machine (cardiopulmonary bypass, CPB). Methods: Twenty consecutive patients were divided into two groups: the first 10 patients received a potential neuroprotective human recombinant erythropoietin, while the remaining 10 comprised the control group. Neurological complications were monitored by measuring serum concentrations of neuropeptide proenkephalin A (PENK-A) and protachykinin A (PTA) before and in the first 5 days after surgery, comparing the neurological outcome with MRI examinations. Results: Both the erythropoietin-treated group and control group were comparable with a non-significant difference shown for the postoperative concentrations of PENK-A and PTA. A comparison of serum concentrations of the biomarkers of 16 patients without brain ischemia and 4 patients with acute ischemia also displayed no significant differences, regardless of erythropoietin therapy. Conclusion: In our pilot study the analysis of PENK-A and PTA serum concentrations might not be the strategy to enable the monitoring and evaluation of neuroprotective stroke treatment, but further studies are required to investigate its role in acute ischemic brain injury.
Keywords: biomarkers; ischemic brain injury; cardiac surgery